2019
DOI: 10.1021/acsami.8b19009
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Electrolyte Additive for High-Voltage LiNi0.5Mn1.5O4 Positive Electrodes

Abstract: 4-(Trimethylsiloxy)-3-pentene-2-one (TMSPO) is tested as an electrolyte additive to enhance Coulombic efficiency and cycle retention for the Li/ LiNi 0.5 Mn 1.5 O 4 (LNMO) half-cell and graphite/LNMO fullcell. TMSPO carries two functional groups, siloxane (−Si− O−) and carbon−carbon (CC) double bonds. It is found that the siloxane group reacts with hydrogen fluoride (HF), which is generated by hydrolysis of lithium hexafluorophosphate (LiPF 6 ) by impure water in the electrolyte solution, to produce 4-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 61 publications
1
73
0
Order By: Relevance
“…Reproduced with permission. [44] Copyright 2019, American Chemical Society. Reproduced with permission.…”
Section: Organosilicon As High/low Temperature Resistance Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [44] Copyright 2019, American Chemical Society. Reproduced with permission.…”
Section: Organosilicon As High/low Temperature Resistance Additivesmentioning
confidence: 99%
“…[42,43] The effectiveness of organosilicon has been proved as a major component or merely an additive in liquid, gel polymer, and solid batteries. [44][45][46] Researchers from University of Wisconsin Madison conducted a lot of valuable researches on organosilicon electrolytes. They investigated the ionic conductivity, [47][48][49][50][51][52][53][54] security, [55][56][57] thermal and electrochemical stability [58][59][60][61] of organosilicon as the solvent and additive in electrolytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23] It is clearly seen that these peaks of LNMO cycled in STE + 0.5 wt %B Ab ecamew eaker than that in STE, which indicatest hat the intensity of PVDF signal is hided and the decomposition of LiPF 6 (LiPF 6 $LiF + PF 5 ,P F 5 + H 2 O! 2HF+ PF 3 O) [53,54] is suppressed with adding BA. The positive phenomenon suggestst hat CEI film has been formed on the LNMO surfacea fter cycled in STE + 0.5 wt %B A.…”
Section: Resultsmentioning
confidence: 99%
“…The working mechanism of bifunctional TMSPO is studied from two aspects: chemistry and electrochemistry (see Figure 8). [101] Studies have revealed that, on the one hand, as HF scavenger, TMSPO additive with bifunctional group can react with HF to generate HPO; on the other hand, the passivation protection layer derived from HPO and TMSPO can inhibit the continuous decomposition of electrolyte and the dissolution of transitional metal, thus improving the Coulomb efficiency and cycling performance of the battery. In addition, (pentafluorophenyl) diphenylphosphine (PFPDPP) as bifunctional additives was presented by Bolloju et.…”
Section: Spinel Tm Oxidesmentioning
confidence: 99%